2012
DOI: 10.1345/aph.1r150
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Metabolic Drug Interactions with Newer Psychotropic Drugs: Inclusion in Package Inserts and Influences of Concurrence in Drug Interaction Screening Software

Abstract: The presence in PIs of DDI information for newer psychotropics appears to have a strong influence on agreement among DDI screening tools. Users of DDI screening software should consult more than 1 source when considering interactions involving generic psychotropics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…Our finding of low agreement across public sources providing PDDI information is concordant with other studies, including the two mentioned in the introduction [7], [8]. Most relevant to the current study, Peters, Bodenreider, and Bahr mapped drugs in the VA NDF-RT, DrugBank, and ONC High-priority list to RxNorm and then examined PDDI overlap [37].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our finding of low agreement across public sources providing PDDI information is concordant with other studies, including the two mentioned in the introduction [7], [8]. Most relevant to the current study, Peters, Bodenreider, and Bahr mapped drugs in the VA NDF-RT, DrugBank, and ONC High-priority list to RxNorm and then examined PDDI overlap [37].…”
Section: Discussionsupporting
confidence: 87%
“…One recent study found that only one quarter of 59 contraindicated drug pairs were listed in three proprietary PDDI information sources [7]. Another recent study comparing drug product labeling to the published literature for information on pharmacokinetic DDIs found that 40% of the 44 pharmacokinetic drug-drug interactions affecting 25 psychotropic drugs were located exclusively in product labeling [8]. These findings suggest that there is a pressing need for informatics research on how to best organize both existing and emerging PDDI information for search and retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…19,20,30-34 These variations have led some researchers to suggest that clinicians use multiple references to overcome the deficiencies of any single product. 33,35 Further examination of these usage patterns might inform improvements that would reduce burdens associated with managing multiple devices and software tools.…”
Section: Discussionmentioning
confidence: 99%
“…a These drugs were chosen because they are very widely prescribed and a number of these “newer” psychotropic drugs are involved in drug-drug interactions [14]. Figure 2 shows the architecture of the proof-of-concept system that we developed for these drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Another concern raised at the conference was that there is currently no standard criteria for evaluating the evidence for interactions. This leads to considerable variation in the drug-drug interactions listed across drug information sources [14]. In future work we plan to develop methods that construct more complete claim-evidence networks for drug-drug interactions that go beyond establishing the potential for the interaction [27], to also provide evidence of the potential risk of harm in patients with specific characteristics.…”
Section: Discussionmentioning
confidence: 99%